<!DOCTYPE HTML PUBLIC "-//W3C//DTD HTML 4.0 Transitional//EN">
<HTML><HEAD><TITLE>[Rasch] 3=4 theorem</TITLE>
<META http-equiv=Content-Type content="text/html; charset=iso-8859-1">
<META content="MSHTML 6.00.6000.16481" name=GENERATOR>
<STYLE></STYLE>
</HEAD>
<BODY bgColor=#ffffff>
<DIV><FONT face=Arial size=2>To be more specific:</FONT></DIV>
<DIV><FONT face=Arial size=2>4*(a+b-c)=3*(a+b-c) can be rewritten 
as</FONT></DIV>
<DIV><FONT face=Arial size=2>4*0=3*0&nbsp; (since a+b=c)</FONT></DIV>
<DIV><FONT face=Arial size=2></FONT>&nbsp;</DIV>
<DIV><FONT face=Arial size=2>You can't go from 4*0=3*0 to 4=3.</FONT></DIV>
<DIV><FONT face=Arial size=2></FONT>&nbsp;</DIV>
<DIV>&nbsp;</DIV>
<BLOCKQUOTE 
style="PADDING-RIGHT: 0px; PADDING-LEFT: 5px; MARGIN-LEFT: 5px; BORDER-LEFT: #000000 2px solid; MARGIN-RIGHT: 0px">
  <DIV style="FONT: 10pt arial">----- Original Message ----- </DIV>
  <DIV 
  style="BACKGROUND: #e4e4e4; FONT: 10pt arial; font-color: black"><B>From:</B> 
  <A title=Stephanou@acer.edu.au href="mailto:Stephanou@acer.edu.au">Stephanou, 
  Andrew</A> </DIV>
  <DIV style="FONT: 10pt arial"><B>To:</B> <A title=rasch@acer.edu.au 
  href="mailto:rasch@acer.edu.au">rasch@acer.edu.au</A> </DIV>
  <DIV style="FONT: 10pt arial"><B>Sent:</B> Wednesday, July 11, 2007 6:54 
  AM</DIV>
  <DIV style="FONT: 10pt arial"><B>Subject:</B> FW: [Rasch] 3=4 theorem</DIV>
  <DIV><BR></DIV>
  <DIV id=idOWAReplyText53481 dir=ltr>
  <DIV dir=ltr><FONT face=Arial color=#000000 size=2>Division by zero is not 
  allowed.</FONT></DIV></DIV>
  <DIV dir=ltr><BR>
  <HR tabIndex=-1>
  <FONT face=Tahoma size=2><B>From:</B> <A 
  href="mailto:rasch-bounces@acer.edu.au">rasch-bounces@acer.edu.au</A> on 
  behalf of Rama Guinda<BR><B>Sent:</B> Tue 7/10/2007 9:31 PM<BR><B>To:</B> 
  rasch<BR><B>Subject:</B> [Rasch] 3=4 theorem<BR></FONT><BR></DIV>
  <DIV>
  <P><FONT size=2>Sorry, I know it's rather irrelevent. But I can't believe it! 
  And I can't<BR>find the flaw in the reasoning either. Besides, I don't know 
  who to ask.<BR>Could you please help?<BR>Thanks<BR>Rama<BR><BR>Three is equal 
  to four<BR>Theorem: 3=4<BR>Proof:<BR><BR>Suppose:<BR>a + b = c<BR><BR>This can 
  also be written as:<BR>4a - 3a + 4b - 3b = 4c - 3c<BR><BR>After 
  reorganizing:<BR>4a + 4b - 4c = 3a + 3b - 3c<BR><BR>Take the constants out of 
  the brackets:<BR>4 * (a+b-c) = 3 * (a+b-c)<BR><BR>Remove the same term left 
  and right:<BR>4 = 
  3<BR><BR>_________________________________________________________________<BR>Tried 
  the new MSN Messenger? Itís cool! Download now.<BR><A 
  href="http://messenger.msn.com/Download/Default.aspx?mkt=en-in">http://messenger.msn.com/Download/Default.aspx?mkt=en-in</A><BR><BR>_______________________________________________<BR>Rasch 
  mailing list<BR>Rasch@acer.edu.au<BR><A 
  href="http://mailinglist.acer.edu.au/mailman/listinfo/rasch">http://mailinglist.acer.edu.au/mailman/listinfo/rasch</A><BR></FONT></P></DIV>
  <P>
  <HR>

  <P></P>_______________________________________________<BR>Rasch mailing 
  list<BR>Rasch@acer.edu.au<BR>http://mailinglist.acer.edu.au/mailman/listinfo/rasch<BR></BLOCKQUOTE></BODY></HTML>